The mousetrap and other plays - Christie, Agatha, 1890-1976. (New York : New American Library, 2000)
This special collection of Agatha Christie's greatest suspense plays includes "The Mousetrap" (the longest running play in history), "Ten Little Indians, Witness for the Prosecution, Appointment with Death, The Hollow, Towards Zero, Go Back to Murder", and "The Verdict."
Ten little Indians -- Appointment with death -- The hollow -- The mousetrap -- Witness for the prosecution --Towards zero -- Verdict -- Go back for murder.
Keywords: Detective and mystery plays, English